Articulating encounters between children and plastics. (November 2022) - Kraftl, Peter; Hadfield-Hill, Sophie; Jarman, Polly; Lynch, Iseult; Menzel, Alice; Till, Ruth; Walker, Amy
In the context of global concerns about plastics, this paper sets out and exemplifies a research agenda for articulating children's encounters with plastics. The paper analyses data co-produced with 11–15 year-olds through interviews, app-based research and experimental/arts-led workshops. It moves beyond scholarship in health and environmental sciences, and in environmental education research, to outline a far richer range of ways to conceptualise children's encounters with plastics, based in children's everyday, embodied and emotive interactions with plastics.